Assessing the effects of diferent training programs for physical preparation and sports performance in power lifters with visual impairments of high qualification - Mariia Roztorhui; Alina Perederiy; Khrystyna Khimenes; Olexandr Tovstonoh (University of Banja Luka, Faculty of physical education and sport, 2021)
Systematic overload, which is a training characteristic of powerlifters with visual impairments of high qualification has a negative impact on the functioning of body systems and the course of the underlying and comorbidities. This determines the relevance of the scientific substantiation of training programs for athletes with visual impairments as the most important component of ensuring the achievement of sports results in powerlifting. This study aimed to experimentally substantiate the effectiveness of the impact of various training programs on physical fitness and athletic performance of powerlifters with visual impairments of high qualification. To solve the goal we used methods of analysis of scientific and methodological literature, pedagogical observation, pedagogical experiment and methods of mathematical statistics. The study involved 16 visually impaired athletes who were members of the national powerlifting team. The pedagogical experiment was based on testing the effectiveness of two training programs, which differed in the parameters of the load components in the annual training and macrocycle periods. After the pedagogical experiment, the experimental group showed reliable indicators of growth on all tests and improvement of sports results, and athletes of the control group increased physical fitness in three tests out of five and sports results are available only in squat and bench press. In both groups, the highest growth rates in the level of development of physical qualities were found in tests aimed at determining the level of development of strength and flexibility. Comparing the results of the introduction of various training programs in the training process of powerlifters with visual impairments, we can conclude that the performance of the experimental group is much higher than among the powerlifters of the control group.